Resultado da propriedade rural x, de sistema composto, nos anos de 2020 e 2021 - Taffarel, Carina (2022)
Agriculture has remained in constant development in recent years. One activity that was modernized a lot was the dairy activity, which started to be carried out in confinement systems, with a specific diet and aimed at greater productivity. With the help of cost accounting, producers began to manage and control costs, seeking greater and better results. This course completion work aims to determine the result of dairy production on rural property X, in the years 2020 and 2021. Thus, this research is classified as descriptive in relation to the objective, as the approach to the problem is classified as qualitative and quantitative and regarding the technical procedure is a case study. Data collection was done by checking documents, invoices and reports, as well as through an interview with the owner. The results obtained show that the producer had an increase in profit of 52.84% from one year to another, due to the increase in sales revenue. Inputs also increased due to the Covid-19 pandemic, where product costs increased by 45.89%. Owners are recommended to always manage their costs so that the activity continues to have positive results.